Human-Centric Policy Evaluation of Jakarta Smart City Initiatives: Enhancing Citizen Engagement to Create Sustainable Public Service - Aflah, Muhammad Fibiyan; Abraham, Juneman (Jurnal Locus Penelitian dan Pengabdian, 2025)
As a rapidly growing metropolis, Jakarta faces challenges in delivering sustainable public services through digital citizen engagement. This study evaluates Jakarta’s smart city initiatives via the JAKI (Jakarta Kini) platform and employs mixed-methods triangulation of descriptive analysis from six stakeholder interviews and 523,321 citizen reports (2021–2024). Findings reveal a 98.73% report completion rate, yet stark regional disparities persist, 27.91% engagement in South Jakarta vs. 0.03% in Kepulauan Seribu, highlighting failures in digital inclusion under Governor Regulation No. 82/2021. The analysis integrates Arnstein’s participation ladder, Norman’s human-centered design, and Wiener’s feedback loops, exposing tokenistic consultation (Level 3) over co-creation. Structural gaps include fragmented system integration (Presidential Regulation No. 95/2018) and trust deficits despite procedural efficiency. The framework proposes hybrid channels (including SMS and face-to-face), participatory roadmaps, and revisions to Governor Regulation No. 68/2022 to prioritize equitable access and iterative feedback. By aligning policy with the human centric concept, Jakarta can transition from City 3.0 (user-centered) to City 4.0 (co-creation), balancing technological efficiency with inclusive governance.